Quality model for educational mobile apps based on SQuaRE and AHP - Del Aguila, Pablo (2022)
During the last decade, there has been an increase in the demand of mobile apps in different download platforms, like Google Play Store, Apple App Store and Amazon App Store. Because of this, different approaches related to mobile app quality have surged, which tend to focus on assessing the general quality of an app without focusing on a specific sector. Because of this reason, the motivation to develop a quality model for mobile apps for the educational sector arises, using the System and Software Quality Requirements and Evaluation (SQuaRE) guidelines and the Analytic Hierarchy Process (AHP) weighting technique; the latter was used to prioritize the quality attributes. A quality model has been obtained, which consists of 8 characteristics, 19 sub-characteristics and 30 metrics. In order to corroborate the proposed model, 4 research questions and 2 case studies related to 2 mobile apps have been established. The results proved that Google Classroom and Moodle have very similar scores in each assessed characteristic; in the case of Usability, there is a difference of 0.006 in favor of Moodle, for Portability, there is a difference of 0.150 in favor of Google Classroom, and for Security, regarding authentication rules and mechanisms, both apps obtained the same result.